1986
DOI: 10.1590/s0034-89101986000100008
|View full text |Cite
|
Sign up to set email alerts
|

Ruralização da Lutzomyia intermedia, um provável caso de pré-adaptação

Abstract: A Lutzomyia intermedia há muito vem sendo encontrada em áreas de colonização antiga. Analisando dados de capturas deste flebotomíneo, com diferentes iscas e em diferentes locais, acredita-se que esta espécie está pré-adaptada a ambientes abertos e a se alimentar em mamíferos, entre eles o homem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
7

Year Published

1987
1987
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 7 publications
0
4
0
7
Order By: Relevance
“…intermedia in disturbed habitats, indicating that this species is able to adapt to deforested environments 27 . Lima 28 suggested that Lu. intermedia was pre-adapted to open habitats, drawing on humans and domestic mammals as blood meal sources.…”
Section: Discussionmentioning
confidence: 99%
“…intermedia in disturbed habitats, indicating that this species is able to adapt to deforested environments 27 . Lima 28 suggested that Lu. intermedia was pre-adapted to open habitats, drawing on humans and domestic mammals as blood meal sources.…”
Section: Discussionmentioning
confidence: 99%
“…withmani are greatly increased in dry rural areas of the interior (Jones et al, 1987), as are populations of Lu. intermedia in coastal and in damp river valleys in rural and peridomiciliary areas (Aragão, 1927;Lima, 1986;Gomes et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…A maioria das espécies do Novo Mundo habita áreas de florestas primárias e ou secundárias, sendo estes locais os possíveis criadouros. Em função das modificações ambientais impostas pelo homem, estes insetos vêm se adaptando a ambientes rurais e periurbanos (Lima, 1986;Brazil et al, 1989 O presente trabalho tem como objetivo conhecer a fauna de flebotomíneos em sete bairros de Timóteo, utilizando para isso armadilha luminosa de New Jersey.…”
Section: Introductionunclassified